Making the Forever War : Marilyn B. Young on the Culture and Politics of American Militarism - Young, Marilyn Blatt (Book collections on Project MUSE., 2021)
"The late historian Marilyn B. Young, a preeminent voice on the history of U.S. military conflict, spent her career reassessing the nature of American global power, its influence on domestic culture and politics, and the consequences felt by those on the receiving end of U.S. military force. At the center of her inquiries was a seeming paradox: How can the United States stay continually at war, yet Americans pay so little attention to this militarism? Making the Forever War brings Young's articles and essays on American war together for the first time, including never before published works. Moving from the first years of the Cold War to Korea, Vietnam, and more recent "forever" wars in Iraq and Afghanistan, Young reveals the ways in which war became ever-present, yet more covert and abstract, particularly as aerial bombings and faceless drone strikes have attained greater strategic value. For Young, U.S. empire persisted because of, not despite, the inattention of most Americans. The collection concludes with an afterword by prominent military historian Andrew Bacevich"--